MODERN METHODS IN TEACHING ENGLISH LANGUAGE (Konferensiyalar | Conferences, 2024)
In today's globalized world, the changes in Uzbekistan's education system are having a big impact in all areas. The government really cares about teaching and improving foreign languages in schools. It's really important for the country's society, economy, politics, and culture. Learning new languages can also make people feel better about their lives. at the government level. A meeting was held over a video call with the President of Uzbekistan.